CHARACTERIZATION OF A FOREST INCENTIVE PORGRAM IN MINAS GERAIS STATE - Rezende, José Luiz Pereira de (2015)
The IEF-Asiflor forest incentive program is the result of a joint endeavor that channeled forest restoration funds to promote, according to effective legislation, silvicultural activity in Minas Gerais state. The above partnership was implemented in 2003. This work aimed to outline the incentive program per participating IEF administrative region, and to georeference and quantify implemented forest stands according to property size class. It was searched data records of all producers benefiting from the program. It was compiled and processed the data, using ArcMap® application to georeference the rural properties making up the sample. The observations concerning number of assisted properties and area reforested in each property per administrative region was based on seven property size classes, according to the 1996 agricultural census classification of the Brazilian Institute of Geography and Statistics (IBGE). The administrative unit showing the largest assisted area was Centro Norte regional office, with 3,872.25 ha, although Zona da Mata regional office had the largest number of benefiting producers, with 449 producers. Featured among the steel producing hubs concentrating the largest number of Asiflor member plants, Sete Lagoas had the largest reforested area, being closer to the actual plants. The most assisted property size class, both in quantity and in area reforested, was class B, except in Centro Norte regional office where Class E showed a larger area reforested.